The impact of prostaglandin analogues on the biomechanical parameters of corneoscleral shell in primary open angle glaucoma - E. N. Iomdina; O. A. Kiseleva; A. Yu. Archakov; I. N. Moiseeva; A. A. Stein (Российский офтальмологический журнал, 2018)
, were measured for 57 patients, including 49 patients aged 51-75 (ave. 66.0 ± 1.7 years) with various stages of POAG and the control group of 8 patients aged 61-68 (ave. 63.7 ± 0.9 years) with no eye pathology (except for age-related cataract). All patients with POAG received hypotensive therapy. Of these, 24 patients received one of prostaglandin analogues (Glauprost) as monotherapy or in combination with beta-blockers and/or carbonic anhydrase inhibitors during no less than 3 months, and 25 patients only received hypotensive therapy beta-blockers and/or carbonic anhydrase inhibitors. The patients’ examination consisted of elastotonometry by Maklakov with three loads having different weights, modified Schiotz differential tonometry using a GlauTest 60 tonograph, measurement of corneal compensated intraocular pressure (IOPcc) and corneal hysteresis (CH) by Ocular Response Analyzer (ORA, Reichert, USA). Results. Coefficient К (2.45 ± 0.15) of patients with stage II POAG (mean age 65.0 ± 1.5 years) who did not use prostaglandin analogues was significantly higher (p < 0.05) than that of patients of the same age group (mean age 66.5 ± 1.8 years) with the same glaucoma stage who received Glauprost (К = 2.09 ± 0.17), which implies a higher risk of glaucoma progression. When prostaglandin analogues were used, CH level proved to be reliably (p < 0.05) higher (9.10 ± 0.4 mm Hg) as compared to patients who received no such therapy (8.14 ± 0.7 mm Hg): this is viewed as a favorable prognostic criterion for the POAG course. A less pronounced decrease of K and increase of CH after prostaglandin analogue instillations than in stage II POAG was also noted in patients with stage III POAG. Conclusion. Prostaglandin analogue Glauprost has a favorable impact on biomechanical parameters of the corneoscleral eye shell, especially in patients with stage II POAG. It lessens glaucoma progression risk induced by disturbed elastic properties of the cornea and the sclera and their ratio // Russian Ophthalmological Journal, 2017; 1: 15-9.